2019
DOI: 10.1021/acs.jmedchem.9b00995
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Binding Assay with an Umbelliferone-Based Fluorescent Rexinoid for Retinoid X Receptor Ligand Screening

Abstract: Ligands for retinoid X receptors (RXRs), "rexinoids", are attracting interest as candidates for therapy of type 2 diabetes, Alzheimer's and Parkinson's diseases. However, current screening methods for rexinoids are slow and require special apparatus or facilities. Here, we created 7-hydroxy-2oxo-6-(3,5,5,8,8-pentamethyl-5,6,7,8-tetrahydronaphthalen-2-yl)-2H-chromene-3-carboxylic acid (10, CU-6PMN) as a new fluorescent RXR agonist and developed a screening system of rexinoids using 10. Compound 10 was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Recently, a coumarin-containing nuclear receptor RXR agonist was reported. The authors demonstrated its utility in a competitive binding assay for several RXR ligands [52]. Coumarins, thus, appear suitable as nuclear receptor ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a coumarin-containing nuclear receptor RXR agonist was reported. The authors demonstrated its utility in a competitive binding assay for several RXR ligands [52]. Coumarins, thus, appear suitable as nuclear receptor ligands.…”
Section: Discussionmentioning
confidence: 99%
“…1 H-NMR (400 MHz, CDCl 3 ): δ 8.88 (1H, d, J = 2.2 Hz), 8.03 (1H, s), 7.96 (1H, dd, J = 9.1, 2.2 Hz), 6.68 (1H, s), 6.23 (1H, d, J = 9.1 Hz), 3.78 (2H, d, J = 6.3 Hz), 3.36 (1H, sep, J = 6.9 Hz), 2.17 (1H, sep, J = 6.6 Hz), 1.32−1.26 (11H, m), 1.07 (6H, d, J = 6.6 Hz). 13 (14). To a solution of 13 (476 mg, 1.20 mmol) in anhydrous DMF (8 mL) were added chloromethyl methyl ether (0.1 mL, 1.3 mmol) and triethylamine (0.18 mL, 1.3 mmol) under an Ar atmosphere.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…22 IC 50 Determination of Test Compounds Using 7. The competitive binding assay using 7 was performed as described 14 with some modifications (see Figure S5). Black 384-well plates purchased from Griner were used (4 wells per sample).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations